Clarifying the Anatomy of the Zygomatic Cutaneous Ligament: Its Application in Midface Rejuvenation. Issue 2 (25th January 2022) - Duan, Jing; Cong, Li-Yao; Luo, Cheng-En; Luo, Sheng-Kang
Abstract : Background: Anatomical knowledge of the zygomatic cutaneous ligament is crucial for rejuvenation of the anteromedial midface. However, there is a lack of satisfactory descriptions of the anatomy of the zygomatic cutaneous ligament, and the exact range and location are still controversial. The present study attempts to clarify the anatomy of the zygomatic cutaneous ligament to provide vital information for clinical operations. Methods: Facial dissection was performed on 36 cadaver hemifaces. The location of the zygomatic cutaneous ligament was investigated and recorded relative to the Frankfort horizontal line and several vertical reference lines. The relative relationship of the zygomatic cutaneous ligament with surrounding anatomical structures was also investigated. Results: The zygomatic cutaneous ligament is a septum-like osteocutaneous ligament originating from the periosteum of the maxilla and zygoma. The overall range of the zygomatic cutaneous ligament starts at the origin of the levator labii superioris and then extends laterally, following the curvature of the inferior bone margin. After merging with the ligamentous part at the origin of zygomaticus minor and zygomaticus major muscle (11.65 mm inferior to the horizontal line), it continues as the zygomatic retaining ligament on the zygomatic arch. The vertical distances between the zygomatic cutaneous ligament and horizontal line along the L1, L2, L3, L4, and L5 reference lines are 9.1, 19.5, 22.1, 21.7, and 18.7 mm, respectively. Conclusion: The anatomical data obtained in the present study regarding the location of the zygomatic cutaneous ligament might be valuable for understanding the appearance of the midcheek fold and be helpful for surgical procedures to rejuvenate the anteromedial midface.